Water Environment Pollution and Control, Volume II (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Water, the lifeblood of our planet, is encountering unprecedented challenges stemming from a diverse array of pollution sources. Water pollution poses signiﬁcant threats to aquatic ecosystems, water quality, and ultimately the health of our planet and its inhabitants. Within the broad framework of “Water Environment Pollution and Control, Volume II” this Special Issue aims to stay informed on pollutant sources and their potential risks in aquatic environments, as well as to develop innovative technologies for pollution control and remediation to establish sustainable solutions for maintaining the health of ecology and humans. We believe the reprint of “Water Environment Pollution and Control, Volume II” will offer readers comprehensive and in-depth knowledge, thereby promoting further research in the field of water environment pollution and control.